Serum decoy receptor 3 levels are associated with the disease activity of MPO-ANCA-associated renal vasculitis. Issue 10 (October 2016) - Maruyama, Hiroshi; Hirayama, Kouichi; Nagai, Miho; Ebihara, Itaru; Shimohata, Homare; Kobayashi, Masaki
Abstract Type 17 T-helper (Th17) cells have been suggested to be involved in the pathogenesis of antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV). Th17 cell proliferation is promoted by tumor necrosis factor (TNF)-like ligand 1A (TL1A), which binds to death receptor 3 (DR3) expressed on Th17 cells. Decoy receptor 3 (DcR3) is known to block the TL1A-DR3 pathway by binding TL1A. To evaluate the Th17-TL1A systems as disease activity markers in AAV, we investigated the serum levels of TL1A and DcR3 in AAV patients. Serum IL-17, IL-23, TL1A, and DcR3 were measured by ELISA in 24 AAV patients with microscopic polyangiitis before the initial treatment, 24 AAV patients during remission, and 20 control subjects. There were no significant differences in serum IL-17, IL-23, and TL1A levels among the active-vasculitis patients, inactive-vasculitis patients, and controls. The mean serum DcR3 level was significantly higher in the active-vasculitis patients than in the inactive-vasculitis patients and controls (P  < 0.0001, respectively). There were significant positive correlations between the serum DcR3 levels and Birmingham Vasculitis Activity Score (BVAS), myeloperoxidase (MPO)-ANCA titers, white blood cell counts, serum creatinine levels, and serum C-reactive protein levels. In a multiple regression analysis, there was a significant positive correlation between the serum DcR3 level and BVAS (β  = 0.650, P  = 0.0462). The mean BVAS level was significantly higher in the active-vasculitis patients with high serum DcR3 levels than in those with the low serum DcR3 levels (P  = 0.0202). The serum level of DcR3 may be a useful marker for disease activity in AAV.